Impact of Acute Normovolemic Hemodilution with Autoplasma Transfusion on Hemostatic Parameters during Abdominal Delivery - T. V. Sheikina; O. V. Rogachevsky; T. K. Puchko; E. M. Shifman (Общая реаниматология)
Objective: to evaluate the impact of acute normovolemic hemodilution (ANH) with autoplasma transfusion on hemostatic parameters during cesarean section. Subjects and methods. The study covered 119 patients in whom ANH was used during cesarean section. Group 1 included 62 women undergoing ANH with autoplasma transfusion; Group 2 (control) comprised 57 pregnant women receiving ANH only. Examination of the hemostatic system involved studies of the plasma link, thromboelastogram readings, vascular platelet hemostasis and evaluation of intravascular thrombogenesis. Results. Transfusion of stored autoplasma as a hemostatic component during ANH favored the development of moderate hypercoagulation due to a significant increase in fibrinogen concentrations by 8%, r+k shortening by 11%, and a rise in the thrombodynamic potential index by 12%. A statistically significant difference has been found in the results between the groups at a stage of surgical hemostasis, which proves the best hemostat-ic effect of ANH used with autoplasma transfusion. Conclusion. The study has demonstrated that the combined use of ANH and autoplasma transfusion contributes to the stabilization of the blood coagulation potential during cesarean section and extends the feasibilities of ANH when the volume of intraoperative blood loss is as high as 25% of the circulating blood volume. Key words: cesarean section, acute normovolemic hemodilution, autoplasma transfusion, coagulation potential.